An Analysis of the Ornstein-Uhlenbeck Process Application to Generate a Pricing Formulae for Tea Derivatives in Nduti Tea Factory. - MUMU, Patrick (Journal of Statistics and Actuarial Research, 2016)
Purpose: The purpose of this study was to analyse a suitable and acceptable model to generate a pricing formulae for tea derivatives. Methodology: The study used descriptive survey research design. This study used secondary data which was collected from Nduti tea factory website. The target population of the study were 318 auction days' observations on the stock exchange spread over from 18/12/2007 to 2/12/2014. Purposive sampling was used to select 6 working days excluding Sundays and holidays starting from 18/12/2014 to 2/12/2014.Data from the websites was analysed using the Ornstein Uhlenbeck process, to derive descriptive results. Results: The findings implied that risk mitigation is an important element that is considered in price derivatives. The study findings indicated that Ornstein-Uhlenbeck Process application to generate a pricing formulae mitigates the risk presented by the fluctuating prices. Further pricing derivatives facilitates the trading of various commodities as a financial instrument. Unique contribution to theory, practice and policy: The study provides the importance which will be emphasized on insuring farmers from uncertainty by ensuring they get value for the input and costs of production. On the other hand, consumers will be protected from the volatile food commodity prices. An incentive for the farmer is established and hence increased and more efficient productivity is witnessed. This leads to designing simple commodity derivatives with different times to expiry for tea in Kenya based on estimated future market prices. The results of this study will be of particular significance to farmers, cooperatives and general investors. The derivatives model proposed in this study can be adopted and used in the agricultural industry especially with regard to tea.